Library mashups: behind the scenes - Bonaria Biancu (JLIS.it, 2010)
The article examines the multiform phenomenon of mashup. The development and diffusion of tools able to integrate and combine data from different systems, creating then new apps and new services is typical of Web 2.0. The paper offers and overview of the technology useful in order to create aggregators, such as API (Application Programming Interface.  Moreover, mashup creation must take into account the most widespread protocols, REST and SOAP to make an example. If there are no APIs available, data reuse is still possible, even though more unsecure: this possibility is pointed out by the presence of feed and the usage of AJAX. Yahoo! Answers is recognized to be a valid example of a tool that offers the possibility of creating a mashup.